Caspase-dependent cleavage and inactivation of the Vav1 proto-oncogene product during apoptosis prevents IL-2 transcription - Hofmann, Thomas G.; Dröge, Wulf (Oncogene, 2000)
Here we identify the hematopoietic proto-oncogene Vav1 as a caspase substrate during apoptosis in lymphoid cells. Cleavage of Vav1 is prevented by the caspase inhibitors zDEVD and zVAD as well as by expression of CrmA. Vav1 is cleaved in vivo at the evolutionary conserved caspase consensus cleavage site DLYD161C, generating the carboxy-terminal cleavage product Vav1p76 of intermediate stability. In vitro caspase assays reveal cleavage of Vav1 at position 161 either by apoptotic cell lysates or by recombinant caspase-3. Mutation of Asp 161 to Ala leads to the usage of the adjacent alternative cleavage sequence DQID150D. Mutation of both cleavage sites at position 150 and 161 protects Vav1 from caspase-mediated proteolysis in vitro and in vivo. The cleavage product Vav1p76 is capable of activating JNK in T-cells, but fails to induce the phosphorylation of p38/HOG1. Vav1p76 displays a diminished capacity to activate the transcription factors NF-AT, AP-1 and NF-κB, and thus completely fails to activate IL-2 transcription. Since Vav1 is essential for IL-2 production and plays a central role for cytoskeletal reorganization, its proteolytic inactivation during apoptosis affects multiple downstream targets.